Optimizing Slaughterhouse (RPH) Retribution Revenue to Support the Regional Original Income of North Toraja Regency - Winta Panimba; Westerini Lusdani (LP2M IAIN Palopo, 2025)
This study aims to analyze the optimization of slaughterhouse (RPH) levy revenue to support the increase in Regional Original Income (PAD) in North Toraja Regency. Slaughterhouse levies are a source of PAD with significant potential, but have not yet made an optimal contribution due to various constraints in their management and collection. Using a qualitative descriptive approach, this study explores the actual conditions of levy collection, the level of utilization of slaughterhouse facilities, and the inhibiting and supporting factors that influence the effectiveness of levy revenue. Data were obtained through interviews, observations, and document reviews related to regulations and regional financial reports. The results indicate that the potential of slaughterhouse levies has not been fully realized due to limited infrastructure, low user compliance, a weak collection administration system, and minimal oversight. On the other hand, there are opportunities to increase revenue through improved service management, regulatory enforcement, facility quality, and strengthened inter-agency coordination. Optimizing slaughterhouse levy revenue requires not only efficiency in the collection process but also improved service quality to make slaughterhouses more attractive to the public and businesses. Thus, optimizing RPH levies has the potential to make a significant contribution to increasing the PAD of North Toraja Regency if managed professionally, transparently, and based on community needs.